CARACTERIZAÇÃO EPIDEMIOLÓGICA DA RAIVA BOVINA NO ESTADO DE MATO GROSSO, BRASIL, NO PERÍODO DE 1996 A 2006 - Matta, G.c.a.; Nociti, D.l.p.; Carvalho, A.a.b. [UNESP]; Nociti, R.p. [UNESP]; Samara, S.i. [UNESP] (Instituto Biológico, 2021)
An epidemiological survey of all cases of bovine rabies that occurred in Mato Grosso, Brazil, during the years 1996 to 2006 was conducted by way of the analysis of the epidemic curve, by calculating the sum, average, standard deviation, maximum and minimum values of the occurrence of rabies in three ecosystems; statistical analysis between the actual cattle in the three biomes of the state and the number of cases of rabies cattle; and the seasonal distribution and disease situation in the state in relation to the national scene. The data were organized by taking into account the month and year of occurrence of rabies and the geographic region of the origin of the material. The different cities involved were classified according to their location in regions of Cerrado, the Pantanal and the Amazon. It was found that the variation in the number of positive cases of the disease has been increasing in recent years, with the largest number of cases occurring in the Cerrado biome, which showed a trend of annual increase. Beginning in the year 2004 the Cerrado ecosystem passed from the situation of enzootic to epizootic, making it evident that the main bovine rabies problem in the state of Mato Grosso is situated in the Cerrado biome.

Um levantamento epidemiológico de todos os casos de raiva bovina ocorridos no Estado de Mato Grosso durante os anos de 1996 a 2006 foi realizado pela análise da curva epidêmica, por meio do cálculo do somatório, média, desvio padrão, valores máximos e mínimos da ocorrência de casos de raiva nos três ecossistemas; análise estatística entre o efetivo bovino nos três biomas do estado e o número de casos de raiva bovina; a distribuição sazonal e a situação da doença no estado em relação ao panorama nacional. Para organização dos dados, levou-se em consideração o mês e o ano de ocorrência da raiva e a região geográfica de origem do material. Os diferentes municípios envolvidos foram classificados conforme sua localização nas regiões de Cerrado, Pantanal e Amazônia. Constatou-se que a variação no número de casos positivos da enfermidade tem sido crescente nos últimos anos, sendo que o maior número de casos deu-se no bioma Cerrado, que apresentou uma tendência de aumento anual. A partir do ano de 2004, o ecossistema Cerrado passou da situação de enzootia para epizootia, ficando pois, evidente que o principal problema de raiva em bovinos no Estado de Mato Grosso está situado no bioma Cerrado.
EPIDEMIOLOGICAL CHARACTERIZATION OF BOVINE RABIES IN THE STATE OF MATO GROSSO, BRASIL, IN THE PERIOD FROM 1996 TO 2006
Keywords: Rabies; cattle; epidemiology; biomes; Mato Grosso; Raiva; bovinos; epidemiologia; biomas; Mato Grosso